The parable of the Widow and the Unjust Judge (Lk 18:1-8) : the significance and relevance of the parable for the experiences of widows in Independent Zimbabwe - Van Eck, Ernest (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2021.